Transforaminal lumbar interbody fusion with cortical bone trajectory screws versus traditional pedicle screws fixation: a study protocol of randomised controlled trial. Issue 10 (22nd October 2017) - Feng, Zhenhua; Li, Xiaobin; Tang, Qian; Wang, Chenggui; Zheng, Wenhao; Zhang, Hui; Wu, Ai-Min; Tian, Naifeng; Wu, Yaosen; Ni, Wenfei
Abstract : Introduction: Transforaminal lumbar interbody fusion (TLIF) has been widely used in the treatment of lumbar degenerative disc disorders and shows favourable clinical results. Recently, cortical bone trajectory (CBT) has become a new trajectory for screw insertion in the lumbar spine. Several biomechanical studies have demonstrated that the CBT technique achieves screw purchase and strength greater than the traditional method. Currently, the available data on the clinical effectiveness of the two performed surgeries, TLIF with CBT screws (CBT-TLIF) and TLIF with traditional pedicle screws (PS-TLIF), are insufficient. This is the first randomised study to compare CBT-TLIF against traditional PS fixation and will provide recommendations for treating patients with lumbar degenerative disc disorders. Methods and analysis: A blinded randomised controlled trial (blinding for the patient and statistician, rather than for the clinician and researcher) will be conducted. A total of 254 participants with lumbar disc degenerative disease who are candidates for TLIF surgery will be randomly allocated to either the CBT-TLIF group or the PS-TLIF group at a ratio of 1:1. The primary clinical outcome measures are the incidence of adjacent cranial facet joint violation, fusion rate and the screw loosening rate. Secondary clinical outcome measures are Visual Analogue Scale (VAS) of back pain, VAS of leg pain, Oswestry Disability Index, operative time, intraoperative blood loss and complications. These parameters will be evaluated on day 3, and then at 1, 3, 6, 12 and 24 months postoperatively. Ethics and dissemination: This study has been reviewed and approved by the Institutional Review Board of the Second Affiliated Hospital and Yuying Children's Hospital of Wenzhou Medical University (batch: 2017–03). The results will be presented in peer-reviewed journals and an international spine-related meeting after completion of the study. Trial registration number: NCT03105167; Pre-results .